Analysis of Environmental Literacy Level of Students at MAN 1 Malang City - Silvi Dwi Pangestu; Mimien Henie Al Muhdhar; Sulisetijono Sulisetijono (BIOEDUKASI, 2023)
Environmental problems that occur today are inseparable from human conditions or interactions with the environment, both biotic and abiotic environments. The low awareness of the Indonesian people towards their environment can also be influenced by their lack of environmental awareness. The purpose of this study is to determine the level of environmental literacy possessed by students of MAN 1 Malang City. This type of research is survey research. The sample of this research was 233 students of class XI and XII majoring in science and social studies. The instrument used in this study was an environmental literacy test adapted from the Middle School Environmental Literacy Survey/Instrument (MSELS). The average value of students' environmental literacy is 57.1 in the currently category.